2005
DOI: 10.1093/jat/29.7.632
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Roadside Urine Drug Screening in Drivers Suspected of Driving Under the Influence of Drugs (DUID)

Abstract: In Belgium, the driving under the influence of drugs (DUID) procedure consists of three steps: observation of external signs of drug consumption by a police officer; an on-site urine test for amphetamines, cannabinoids, cocaine, and opiates; and blood sampling by a physician for gas chromatography-mass spectrometry analysis. The driver is sanctioned if THC is greater than 2 ng/mL, morphine is greater than 20 ng/mL, or amphetamine, methylenedioxymethamphetamine (MDMA), methylenedioxyethylamphetamine, N-methyl-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 5 publications
1
17
2
1
Order By: Relevance
“…Detection of this group depends on the perception of the police officers and additionally there are remarkable differences between countries, probably because of different national road traffic acts and levels of attention to the problem. The prevalence for COC abuse in the present study is higher than in most other reports with a rate between 0.1 and 8.4% [37][38][39][40][41][42][43][44][45][46][47][48], but in the US [49,50], Belgium [51,52], the Netherlands [53], Switzerland [54], and Germany [36,55] a higher prevalence was found between 10.2 and 32.7%.…”
Section: Discussioncontrasting
confidence: 71%
“…Detection of this group depends on the perception of the police officers and additionally there are remarkable differences between countries, probably because of different national road traffic acts and levels of attention to the problem. The prevalence for COC abuse in the present study is higher than in most other reports with a rate between 0.1 and 8.4% [37][38][39][40][41][42][43][44][45][46][47][48], but in the US [49,50], Belgium [51,52], the Netherlands [53], Switzerland [54], and Germany [36,55] a higher prevalence was found between 10.2 and 32.7%.…”
Section: Discussioncontrasting
confidence: 71%
“…Cannabis is a widely used drug and earlier research showed that THC is the most prevalent drug among impaired drivers in Belgium, followed by amphetamine and ecstasy [11]. In this study opiates follow THC regarding prevalence, but this was also as expected, since the majority of the recruited drug addicts come to the rehabilitation centre for methadone substitution, to control their heroin addiction.…”
Section: Discussionsupporting
confidence: 65%
“…In general, studies considering toxicological analysis of biological specimens involve collections of samples from drivers suspected of driving under the influence of alcohol/drugs or involved in accidents (Holmgren et al 2007;Raes and Verstraete 2005;Romano and Voas 2011). However, some studies have considered the analysis of biological samples from the general driving populations to estimate the prevalence of alcohol/drug use.…”
Section: Introductionmentioning
confidence: 99%